Improving critical response in ndonesian hospitals through martha’s rule - Asnaningsih, Ambar (Science Midwifery, 2025)
Delays in recognizing and responding to clinical deterioration remain a leading cause of preventable harm in hospitals, particularly in systems where patients and families lack the authority to escalate care concerns. While the United Kingdom’s introduction of Martha’s Rule has provided a model for patient- and family-initiated escalation systems, the feasibility of implementing such frameworks in middle-income countries like Indonesia remains uncertain. This study conducted a structured narrative review of international literature from 2014 to 2024, analyzing activation rates, timeliness of response, patient satisfaction, and outcome improvements across ten health systems. Results show that countries with institutionalized escalation policies—such as New Zealand, Australia, and the UK—demonstrate measurable improvements in clinical responsiveness and trust. By contrast, Indonesia exhibits low utilization, hindered by regulatory gaps, workforce limitations, and cultural barriers. However, pilot programs in private hospitals suggest that family escalation systems can be successfully adapted. This review concludes that while Martha’s Rule offers a valuable pathway for improving patient safety, its success in Indonesia will depend on phased implementation, cultural alignment, staff training, and strong policy support.